The medial afterlives of H.P. Lovecraft comic, film, podcast, TV, games - Lanzendörfer, Tim; Dreysse Passos de Carvalho, Max José (Palgrave Macmillan, 2023)
Medial Afterlives of H.P. Lovecraft brings together essays on the theory and practice of adapting H.P. Lovecraft's fiction and the Lovecraftian. It draws on recent adaptation theory as well as broader discourses around media affordances to give an overview over the presence of Lovecraft in contemporary media as well as the importance of contemporary media in shaping what we take Lovecrafts legacy to be. Discussing a wide array of medial forms, from film and TV to comics, podcasts, and video and board games, and bringing together an international group of scholars, the volume analyzes individual instances of adaptation as well as the larger concern of what it is possible to learn about adaptation from the example of H.P. Lovecraft, and how we construct Lovecraft and the Lovecraftian today in adaptation. Medial Afterlives of H.P. Lovecraft is focused on an academic audience, but it will nonetheless hold interest for all readers interested in Lovecraft today. Tim Lanzendorfer is research assistant professor of American Studies at Goethe University, Frankfurt, Germany. He has published widely in contemporary literature and media. His most recent books are the forthcoming Utopian Pasts and Futures in the Contemporary American Novel (2023) and the Routledge Companion to the British and North American Literary Magazine (2021). Max Jose Dreysse Passos do Carvalho is a graduate student of American Studies at Goethe University, Frankfurt, Germany. His research and forthcoming publications concentrates on game studies and philosophy
Keywords: Lovecraft, H. P. -- 1890-1937; Intermedialität; Adaption -- Literatur; Rezeption; Lovecraft, H. P. / (Howard Phillips) / 1890-1937 / Adaptations; Lovecraft, H. P. / (Howard Phillips) / 1890-1937 / Influence; Horror in mass media; Horror in literature; Horror in art; Lovecraft, H. P. / (Howard Phillips) / 1890-1937; Influence (Literary, artistic, etc.); Adaptations; Aufsatzsammlung